2007
DOI: 10.1091/mbc.e06-09-0846
|View full text |Cite
|
Sign up to set email alerts
|

Subnuclear Localization and Dynamics of the Pre-mRNA 3′ End Processing Factor Mammalian Cleavage Factor I 68-kDa Subunit

Abstract: Mammalian cleavage factor I (CF I m ) is an essential factor that is required for the first step in pre-mRNA 3 end processing. Here, we characterize CF I m 68 subnuclear distribution and mobility. Fluorescence microscopy reveals that in addition to paraspeckles CF I m 68 accumulates in structures that partially overlap with nuclear speckles. Analysis of synchronized cells shows that CF I m 68 distribution in speckles and paraspeckles varies during the cell cycle. At an ultrastructural level, CF I m 68 is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
65
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 42 publications
10
65
2
Order By: Relevance
“…In this report we provide first evidence that the 68-kDa subunit of CF I m , a pre-mRNA 3Ј end processing factor, interacts with the mRNA export receptor NXF1 and stimulates mRNA export. On the basis of our observations and on previous data showing that CF I m 68 is associated with BrdU-labeled nascent transcripts (Cardinale et al, 2007), we propose that CF I m 68 is loaded onto the pre-mRNA during cleavage and polyadenylation of the 3Ј end of the transcript and remains bound to the mRNA all the way to the cytoplasm where it is removed by the translation machinery. CF I m 68 may thus act as a mark of correct 3Ј end maturation and contribute to efficient mRNA export via NXF1 recruitment.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In this report we provide first evidence that the 68-kDa subunit of CF I m , a pre-mRNA 3Ј end processing factor, interacts with the mRNA export receptor NXF1 and stimulates mRNA export. On the basis of our observations and on previous data showing that CF I m 68 is associated with BrdU-labeled nascent transcripts (Cardinale et al, 2007), we propose that CF I m 68 is loaded onto the pre-mRNA during cleavage and polyadenylation of the 3Ј end of the transcript and remains bound to the mRNA all the way to the cytoplasm where it is removed by the translation machinery. CF I m 68 may thus act as a mark of correct 3Ј end maturation and contribute to efficient mRNA export via NXF1 recruitment.…”
Section: Discussionsupporting
confidence: 72%
“…Therefore, it is possible that CF I m 68 is leaving the nucleus by "piggy-backing" on RNA molecules being exported by other factors, either in association with the 25-kDa subunit or because of a direct interaction via the C-terminal domain. To determine whether shuttling of CF I m 68 depends on mRNA synthesis, we performed heterokaryon assays in the presence of actinomycin D. As shown in Figure 2B, GFP-CF I m 68 shuttling is blocked in presence of the transcription inhibitor, whereas relocalization of the protein in cap-like structures around the nucleoli of the human cell can be observed, as previously described (Cardinale et al, 2007; Figure 2B). Although we cannot formally rule out the possibility that actinomycin D could affect the synthesis of a short-lived protein required for export, the most likely conclusion of these experiments is that CF I m 68 shuttling is dependent on mRNA synthesis and possibly export.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…An increasing number of studies have shown that dynamic and distinct nuclear compartments are likely to be associated with various pre-mRNA processing activities in many cell types (Boronenkov et al, 1998;Cardinale et al, 2007;Huang and Spector, 1991;Huang and Spector, 1992;Lamond and Spector, 2003;Mellman et al, 2008;Mintz and Spector, 2000;Politz et al, 2006). SYDN-1 could negatively regulate NpolyA activity on selected transcripts via direct interaction with PFS-2, or indirectly via additional proteins.…”
Section: Subnuclear Compartmentalization In Neuronsmentioning
confidence: 99%
“…The CF I m 25 dimer together with one of the two larger subunits is sufficient to stimulate cleavage, although it is not known in what function the large subunits differ (Rüegsegger et al 1996(Rüegsegger et al , 1998. Analysis of the subnuclear localization of CF I m 68 has identified this protein in speckles and paraspeckles and its location varies during the cell cycle (Cardinale et al 2007). Moreover, sequence-specific RNA binding of the CF I m 68 subunit to motifs within the 39 UTR of its own premRNA has been reported to suppress cleavage (Brown and Gilmartin 2003).…”
Section: Introductionmentioning
confidence: 99%